Gendered Laws, Informal Origins, and Subsequent Performance - Hyland, Marie (World Bank, Washington, DC, 2021)
This research explores the relationship between laws that discriminate on the basis of gender and the probability that a female-owned business begins operating in the informal sector. This is achieved by tracing the origins of formal businesses surveyed in the World Bank Enterprise Surveys and merging this with information on the level of legal equality between genders as measured by the Women, Business and the Law database. In addition, the research explores whether starting a business informally has any differential effect on subsequent firm performance depending on the gender of the owner(s). The results show that gender discriminatory laws increase the likelihood that firms with female owners will begin operations in the informal sector; as expected, this does not hold for enterprises that are solely owned by men. Furthermore, the research provides evidence that firms that began operations informally have poorer performance years later—a relationship that exists both for firms with female owners and for firms fully owned by men. The results show notable variation by region.